Localization and hormonal regulation of endometrial matrix metalloproteinase-26 in the rhesus macaque - Almeida-Francia, C. C. D. [UNESP]; Keator, C. S.; Mah, K.; Holden, L.; Hergert, C.; Slayden, O. D. (Oxford University Press, 2012)
The current understanding of hormonal regulation of matrix metalloproteinase-26 (MMP-26) in the primate endometrium is incomplete. The goal of this work was to clarify estrogen and progesterone regulation of MMP-26 in the endometrium of ovariectomized, hormone-treated rhesus macaques.Ovariectomized rhesus macaques (n 66) were treated with estradiol (E-2), E-2 plus progesterone, E-2 followed by progesterone alone or no hormone. Endometrium was collected from the hormone-treated animals during the early, mid- and late proliferative and secretory phases of the artificial menstrual cycle. MMP-26 expression was quantified by real-time PCR, and MMP-26 transcript and protein were localized by in situ hybridization and immunohistochemistry and correlated with estrogen receptor 1 and progesterone receptor (PGR).MMP-26 was localized to glandular epithelium and was undetectable in the endometrial stroma and vasculature. MMP-26 transcript levels were minimal in the hormone-deprived macaques and treatment with E-2 alone did not affect MMP-26 levels. Treatment with progesterone both in the presence and absence of E-2 stimulated MMP-26 expression in the early and mid-secretory phases (P 0.001). MMP-26 expression preceded decidualization of endometrial stroma. MMP-26 levels then declined to baseline in the late secretory phase (P 0.01) despite continued E-2 plus progesterone treatment. Loss of detectable MMP-26 expression in the late secretory phase was correlated with late secretory phase loss of glandular epithelial PGR.Endometrial MMP-26 expression is dependent on the presence of progesterone in the early secretory phase and then gradually becomes refractory to progesterone stimulation in the late secretory phase. In the macaque, MMP-26 is a marker of the pre-decidual, secretory endometrium. During the second half of the late secretory phase, and during decidualization, MMP-26 loses its response to progesterone concurrent with the loss of epithelial PGR. The decline in MMP-26 levels between the mid- and late secretory phases may play a role in the receptive window for embryo implantation.
Keywords: matrix metalloproteinase-26; estradiol; progesterone; rhesus macaque; endometrium